The effects of Yucca schidigera and Quillaja saponaria on growth performance and enzymes activities of juvenile shrimp Litopenaeus vannamei cultured in low-salinity water - Hernández-Acosta,Mario (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2016)
ABSTRACT. The inclusion of Yucca schidigera and Quillaja saponaria extracts (NTF) in aquatic organisms display a positive response on production and organism's physiology. Fifteen tanks (140 L) with low-salinity water (S = 5) were stocked with 10 juvenile shrimp (Litopenaeus vannamei, 2.6 g of mean weight) feeding with 0, 0.25, 0.5, 1.0 and 2.0 g kg-1 of NTF of basal diet (triplicate treatment). The shrimp were cultured in a close recirculation system (control condition) and fed ad libitum daily for 40 days. General growth parameters (body weight, growth, body length, feed conversion rate, survival) and hepatopancreatic digestive enzyme activities (alkaline protease, alkaline phosphatase, a-amylase, leucine aminopeptidase, and lipase) were evaluated after 40 days of shrimp culture. The final mean body weight, individual mean body, weight gain, and feed conversion ratio from shrimp feeding with 1.0 and 2.0 g kg-1 of NTF have a significant (P < 0.05) result compared to other treatments. The highest values of alkaline protease, lipase, and a-amylase were detected in shrimp feeding with 0.5 g kg-1 of NTF, where a high level of leucine aminopeptidase and alkaline phosphatase were detected with 0.25 g kg-1 of NTF treatment. However, any significant differences in enzyme activities were detected between the control group and treatments. The increase effect in shrimp growth and any decrease effect in enzyme activity detected in present study suggest that NTF shows potential as a feed additive for shrimp cultured at low-salinity.